Free and copolymerized gamma-cyclodextrins regulate performance of dexamethasone-loaded dextran microspheres for bone regeneration - Lima, A. C. (2014)
Polymeric particles acting as source of biological cues to promote tissue regeneration are currently an interesting topic in bone tissue engineering research. In this study, microspheres of dextran-methacrylated (dextran-MA) and γ-cyclodextrins (γ-CD) for the delivery of osteogenic agents were prepared by means of photopolymerization on biomimetic superhydrophobic surfaces. The effects of the incorporation of the γ-CD units as free entities or as structural monomers (acrylamidomethyl-γ-cyclodextrin, γ-CD-NMA) on dexamethasone loading and release performance were evaluated in detail in order to achieve osteogenic differentiation of human stem cells. The copolymerization of dextran-MA with γ-CD-NMA improved the loading capacity of the particles and also provided a sustained release of dexamethasone for several days. The biological studies revealed that such microspheres were cytocompatible and capable to induce the differentiation of human adipose-derived stem cells (hASCs) to osteoblasts, as determined from an increase of alkaline phosphatase (ALP) activity between days 3 and 7. Such results were also confirmed using ALP staining. Therefore, immobilization of γ-CDs onto dextran-MA network may be particularly useful for the development of cytocompatible implantable spherical biomaterials for bone tissue engineering purposes.